(untitled) (Research, Society and Development, 2021)
This paper proposes an interdisciplinary strategy for teaching Cell Biology in high school through using artistic expressions and active methodologies. For this, to receive classes on the content of Cell Biology were selected control and experimental groups of 1st-year high school students from the public high school system of the Distrito Federal. In the control class, the content approach was made in an expositive way, with the organization of the students in seminars. This was a way that they already used in the school context of Biology classes. In the experimental group, there was the work with projects using artistic expressions and the development of educational products as a result of their learning about the themes related to Cell Biology. The art production included parodies, scale models, comics, drawings, and theater. An evaluation test applied to both groups revealed promising and statistically significant results for the student’s learning from the experimental class concerning the control class. Furthermore, a questionnaire answered by them allows us to verify that the artistic expressions use motivated and awakened interest and involved and united all the students around the production.